ANALISIS RASIO LIKUIDITAS DAN LEVERAGE RATIO TERHADAP PROFITABILITAS PADA PT BENTOP LEGIUN YAKIN DI KOTA BATAM - Patryn, Patryn; Natalia, Erni Yanti (LPPM Universitas Putera Batam, 2021)
The purpose of this research is to analyze the liquidity ratio and leverage ratio to profitability at PT. Bentop Legion Yakin that located in Batam which was held from January 2016 to December 2020. The purpose of this research is to analyze the relationship between quick ratio and ROA, DAR with ROA, DER with ROA and all role quick ratio, DAR and DER with ROA. The data used in analyzing this research is a sample which using purposive sampling technique as data collection method, the data method used in analyzing this research is quantitative analysis and research methods with the population in the study are 60 data and data analysis techniques used with the Statistics Package program to Social Sciences (SPSS) version 25 which were used to provide a clear description of the relationship of all variables. From the research methods used in this study, it can be seen that this study shows that the quick ratio and DER variables can partially affect significantly to the ROA and all roles together will impact on assets.